Acceptance of E-learning Technology by Using the Technology Acceptance Model (TAM) Method - Ibrahim Hasan; Sait Abdullah; Darojat Tubagus Ahmad (International Journal of Science and Environment (IJSE), 2025)
The main aim of the study is to investigate the relationship between the variables included in the Technology Acceptance Model (TAM), and the core variables and the extended variables of the TAM. The research method is a quantitative research that tests hypotheses derived from variables extracted from the Technology Acceptance Model (TAM), which include the variables of perceived ease of use, perceived usefulness, attitude towards use, actual use, e-learning self- efficiency, and a set of variables. complexity To test the relationship between each variable, this study uses statistical tests using structural equation modeling (SEM) application tools SmartPLS. The results of the research hypothesis are (H1) the positive effect of e-learning self-efficacy (learning self-efficacy online) on the perception of comfort (perceived ease of use). (H2) positive effect of e-learning self-efficacy on perceived usefulness (perceived usefulness), (H3) positive effect of complexity on perceived ease of use. (H4) complexity has a positive effect on perceived usefulness. (H5) perception of ease of use (perceived ease of use) the use of e-learning affects the attitude to use (attitude to use). (H6) view of usefulness (perceived usefulness) positive effect of e-learning on usage attitude (attitude towards usage). (H7) perceived ease (perceived ease of use) negative effect on actual use e-learning (actual use). (H8) perceived usefulness of e-learning (perceived usefulness) positively affects actual use (actual use). (H9) usage attitude (attitude towards usage) positive effect on actual usage (actual usage). The practical implication of the research include conducting an extension study of external TAM variables, conducting a study with different objects and subjects and conducting a pretest of the samples to be studied in the prior to the research.